Analysis of Maternal Nutritional Status in Relation to Stunting Incidence as a Preventive Effort during the First 1000 Days of Life - Indah Yun Diniaty Rosidi; Rajia Rajia; Harnaningsi Harnaningsi (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Undernutrition and stunting are interrelated conditions that can affect the quality of human resources. These problems indirectly contribute to high maternal, infant, and under-five mortality rates, as well as low life expectancy. This study aimed to analyze the relationship between maternal nutritional status and the incidence of stunting in Boneatiro Village, Kapontori Subdistrict, Buton Regency, Southeast Sulawesi. This study was conducted in Boneatiro Village with a population of 123 children under five. A total of 40 respondents were selected using purposive sampling. The study employed a case-control design with a retrospective approach. Data were collected through interviews and observations of Maternal and Child Health (MCH) books. Data analysis was performed using descriptive statistics, as well as bivariate and multivariate analyses (Chi-square test and ordinal logistic regression). The Chi-square test showed a significant association between maternal body mass index (BMI) (p = 0.022) and chronic energy deficiency (CED) (p = 0.011) with the incidence of stunting. The ordinal logistic regression analysis indicated that maternal nutritional status had a significant effect on stunting in children, with p = 0.025 (95% CI −4.875 to −0.328) for BMI and p = 0.005 (95% CI −3.137 to −0.566) for CED. In conclusion, maternal nutritional status during pregnancy, particularly underweight conditions and CED, significantly influenced the incidence of stunting in children. Mothers with poor nutritional status had a higher risk of delivering stunted children, especially those classified as severely stunted.